2015
DOI: 10.1002/adma.201502864
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Sodium‐Ion Battery Composed of Carbon Coated Na3V2(PO4)3 in a Porous Graphene Network

Abstract: A 3D hierarchical meso- and macroporous Na3V2(PO4)3-based hybrid cathode with connected Na ion/electron pathways is developed for ultra-fast charge and discharge sodium-ion batteries. It delivers an excellent rate capability (e.g., 86 mA h g(-1) at 100 C) and outstanding cycling stability (e.g., 64% retention after 10,000 cycles at 100 C), indicating its superiority in practical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
320
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 490 publications
(332 citation statements)
references
References 44 publications
11
320
1
Order By: Relevance
“…The one‐dimensional sodium ion transport pathway and the highly conductive network can further improve the electrochemical performance greatly. Due to its remarkably high conductivity and mechanical properties, graphene was also introduced to improve the performance of the Na 3 V 2 (PO 4 ) 3 electrode,12, 83, 105, 109, 110, 111, 112, 113 for example, Jung and Tao et al have reported a graphene‐supported Na 3 V 2 (PO 4 ) 3 with a rate capability of 30 C and a stable cycling performance over 300 cycles 109, 110…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
See 3 more Smart Citations
“…The one‐dimensional sodium ion transport pathway and the highly conductive network can further improve the electrochemical performance greatly. Due to its remarkably high conductivity and mechanical properties, graphene was also introduced to improve the performance of the Na 3 V 2 (PO 4 ) 3 electrode,12, 83, 105, 109, 110, 111, 112, 113 for example, Jung and Tao et al have reported a graphene‐supported Na 3 V 2 (PO 4 ) 3 with a rate capability of 30 C and a stable cycling performance over 300 cycles 109, 110…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
“…Recently, the use of hierarchical carbon to decorate the Na 3 V 2 (PO 4 ) 3 electrode has been widely adopted to make high‐performance Na 3 V 2 (PO 4 ) 3 electrodes 11, 12, 60, 105, 111, 112, 113, 114, 115, 116. Zhu et al reported a carbon‐coated Na 3 V 2 (PO 4 ) 3 embedded in porous carbon with remarkable rate capability of 44 mAh g –1 at a current rate of 200 C ( Figure 6 d) 114.…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
See 2 more Smart Citations
“…[149] In order to reduce the irreversible capacity of the full cells, presodiation of Sb-and Sn-based anodes was employed prior to assembling the full cell. [74][75][76][77][78][79][80][81] For example, the NiSb//Na 0. 4 , with capacity retention of 75% after 20 cycles.…”
Section: Asymmetric Sodium-ion Full-cell System Based On Presodiated mentioning
confidence: 99%